Investigation of Perceived External UAM Design Features as a New Transportation Method. (September 2022) - Chun, Nathan; Jachim, Nate; Park, GeeBeum; Kim, Sang-Hwan
Urban air mobility (UAM) has been suggested as a new method of transportation to solve issues of rising populations and traffic congestion in metropolitan areas. UAM is mostly conceptual, as there is no standardization for the external aesthetic features of a UAM. This study aims to understand how people would perceive and describe the external design of UAM and how specific features of UAM design associate with the descriptor terms and preference by adopting the methods of Kansei Engineering or Measure of Perception. Participants were asked to rate different sample UAM designs using 30 semantic pairs selected to best describe UAM. The factor results on the semantic pairs revealed five descriptor terms including safety, comfort, novelty, simplicity, and its level of advancement. The results also found that participants prefer the sample designs that generate feelings of safety, comfort, and simplicity, with a few advancements. Even though the study is preliminary, the study can be extended to understand users' mental models and apply them to the effective design of UAM in various ways.